Serumski cistatin C - nov označevalec glomerulne filtracije - Bevc, Sebastjan (Medicinski razgledi, 2006)
The glomerular filtration rate (GFR) is the main indicator of kidney function and GFR estimation is essential for the evaluation of patients with chronic kidney disease. In clinical practice, serum creatinine levels and creatinine clearance are the most commonly used markers to estimate GFR. The standard GFR estimation method is based on the clearance of a radionuclide-labelled marker. Recently, serum cystatin C has been proposed as a new endogenous GFR marker. This protease inhibitor with a low molecular weight is produced at a constant rate by all nucleated cells and is freely filtered across the glomerular membrane. Contrary to serum creatinine, serum cystatin C does not depend on muscle mass, sex, age or dietary protein intake. This study confirmed that serum cystatin C is a reliable marker of GFR. Serum cystatin C had a higher diagnostic accuracy than serum creatinine and also creatinine clearance in well-defined patients with chronic kidney disease.
Keywords: Kidney Diseases; Ledvica, bolezni; Glomerularna filtracija, hitrost; diagnosis; Diagnostika; Cistatini; Glomerular Filtration Rate; Kreatinin; ledvične bolezni; Cystatins; glomerulna filtracija; Creatinine